Students’ Perceptions of Artificial Intelligence in Tax Learning - Wisesa, Panca; Wulan, Diajeng Fitri; Ladista, Rindy Dwi; Sidik, M. Muhayin A (ISAS, 2025)
The use of Artificial Intelligence (AI) in higher education has increased rapidly, with many students using AI-based applications independently to support learning. In regulation-based subjects such as taxation, this practice raises concerns related to learning accuracy, relevance to local regulations, and ethical use. This study aims to examine students’ perceptions of AI use in tax learning. A qualitative descriptive approach was employed involving undergraduate accounting and taxation students at the University of Lampung and the Lampung State Polytechnic who had taken taxation courses and used AI as a learning tool. Using purposive sampling, data were collected through an online questionnaire, resulting in 143 valid responses from an estimated eligible population of 809 students. The questionnaire included Likert-scale items and open-ended questions, with qualitative data analyzed using thematic analysis. The findings indicate that students perceive AI as a helpful learning support, particularly for understanding complex tax regulations, improving learning efficiency, and supporting independent study. However, concerns remain regarding information accuracy, limited relevance to Indonesian tax regulations, overreliance on AI, and academic integrity. This study concludes that AI can support tax learning when used as a complementary tool, supported by critical use and lecturer guidance. Keywords: artificial intelligence; student perceptions; tax learning; higher education; qualitative research